Atomic layer deposition on dental materials: Processing conditions and surface functionalization to improve physical, chemical, and clinical properties - A review - Hashemi Astaneh, Sarah; Faverani, Leonardo P. [UNESP]; Sukotjo, Cortino; Takoudis, Christos G. (Elsevier, 2021)
Surface functionalization is an effective approach to improve and enhance the properties of dental materials. A review of atomic layer deposition (ALD) in the field of dental materials is presented. ALD is a well-established thin film deposition technique. It is being used for surface functionalization in different technologies and biological related applications. With film thickness control down to Ångström length scale and uniform conformal thin films even on complex 3D substrates, high quality thin films and their reproducibility are noteworthy advantages of ALD over other thin film deposition methods. Low temperature ALD allows temperature sensitive substrates to be functionalized with high quality ultra-thin films too. In the current work, ALD is elaborated as a promising method for surface modification of dental materials. Different aspects of conventional dental materials that can be enhanced using ALD are discussed. Also, the influence of different ALD thin films and their microstructure on the surface properties, corrosion-resistance, antibacterial activity, biofilm formation, and osteoblast compatibility are addressed. Depending on the stage of advancement for the studied materials reported in the literature, these studies are then categorized into four stages: fabrication & characterization, in vitro studies, in vivo studies, and human tests. Materials coated with ALD thin films with potential dental applications are also presented here and they are categorized as stage 1. The purpose of this review is to organize and present the up to date ALD research on dental materials. The current study can serve as a guide for future work on using ALD for surface functionalization and resulting property tuning of materials in real world dental applications.
Keywords: Antibacterial; Atomic layer deposition; Dental implants; Osteointegration; Surface functionalization